Modification of Kraft Lignin with Dodecyl Glycidyl Ether - Alwadani, Norah S. (ChemistryOpen, 2019)
Kraft lignin (KL) is extensively produced in industry but is mainly burned as fuel. To broaden its use, KL was grafted with dodecyl glycidyl ether to alter its thermal properties. The reaction of KL with dodecyl glycidyl ether (DGE) was analyzed using nuclear magnetic resonance (NMR), Fourier infrared spectroscopy (FT‐IR) and elemental analysis. Alternatively, KL was methylated to mask its phenolic hydroxy groups to investigate how phenolic hydroxy groups impact the grafting of the alkyl chain of DGE onto lignin (methylated Kraft lignin, MKL). The methylation facilitated the molecular weight enhancement and thermal stability reduction of Kraft lignin via grafting with DGE. The influence of grafting alkyl chains on the structural and thermal properties of KL and MKL was studied using thermogravimetric analysis and differential scanning calorimetry analysis. Our data suggest that, due to their high molecular weights and lower glass transition temperatures, the produced lignin derivatives may be promising feedstocks for composite production.